Viral Lesions of Oral Cavity - Sudakshina Mukherjee1 , N. Aravindha Babu2 , E. Rajesh3, K.M.K.Masthan4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Oral examination is an integral part of general dentistry. So it is not uncommon to come across various viraldiseases in the oral cavity. The clinical diagnosis of these viral lesions sometimes become confusing dueto similar clinical presentations, confusion leads to misdiagnosis and eventually the treatment.This articlediscusses about the viral lesions, their clinical presentation, diagnosis and appropriate management whichare usually manifested in oral cavity that will eventually provide the general dental practitioner with an upto date guide for better diagnosis and management.